The Art of Counselling and Psychotherapy - Holm-Hadulla, Rainer M. (EBL-Schweitzer, 2004)
COVER; ABOUT THE AUTHOR; FOREWORD; CHAPTER ONE: Introduction and overview; CHAPTER TWO: Creativity; CHAPTER THREE: Three examples of counselling and psychotherapy; CHAPTER FOUR: Hermeneutics: the art of creative understanding and life management; CHAPTER FIVE: Aesthetic experience and shaping of reality; CHAPTER SIX: Creative principles of psychotherapy; CHAPTER SEVEN: Creative principles of counselling and coaching; CHAPTER EIGHT: The creative aspect of brief dynamic psychotherapy; CHAPTER NINE: The creative aspect of psychoanalysis